An integrated approach to care attracts people living with HIV who use illicit drugs in an urban centre with a concentrated HIV epidemic. Issue 1 (December 2016) - Fernando, S.; McNeil, R.; Closson, K.; Samji, H.; Kirkland, S.; Strike, C.; Turje, R.; Zhang, W.; Hogg, R.; Parashar, S.
Abstract Background People living with HIV (PLHIV) who are also marginalized by social and structural inequities often face barriers to accessing and adhering to HIV treatment and care. The Dr. Peter Centre (DPC) is a non-profit integrated care facility with a supervised injection room that serves PLHIV experiencing multiple barriers to social and health services in Vancouver, Canada. This study examines whether the DPC is successful in drawing in PLHIV with complex health issues, including addiction. Methods Using data collected by the Longitudinal Investigations into Supportive and Ancillary health services (LISA) study from July 2007 to January 2010, linked with clinical variables available through the British Columbia Centre for Excellence in HIV/AIDS Drug Treatment Program, we identified DPC and non-DPC clients with a history of injection drug use. Bivariable and multivariable logistic regression analyses compared socio-demographic and clinical characteristics of DPC clients (n  = 76) and non-DPC clients (n  = 482) with a history of injection drug use. Results Of the 917 LISA participants included within this analysis, 100 (10.9%) reported being a DPC client, of which 76 reported a history of injection drug use. Adjusted results found that compared to non-DPC clients with a history of injection drug use, DPC-clients were more likely to be male (AOR: 4.18, 95% CI = 2.09–8.37); use supportive services daily vs. less than daily (AOR: 3.16, 95% CI = 1.79–5.61); to have been diagnosed with a mental health disorder (AOR: 2.11; 95% CI: 1.12–3.99); to have a history of interpersonal violence (AOR: 2.76; 95% CI: 1.23–6.19); and to have ever experienced ART interruption longer than 1 year (AOR: 2.39; 95% CI: 1.38–4.15). Conclusions Our analyses suggest that the DPC operating care model engages PLHIV with complex care needs, highlighting that integrated care facilities are needed to support the multiple intersecting vulnerabilities faced by PLHIV with a history of injection drug use living within urban centres in North America and beyond.